2008
DOI: 10.1007/s00421-008-0850-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the rate of heat storage on serum heat shock protein 72 in humans

Abstract: Hsp72 concentration has been shown to be higher in the serum (eHsp72) of runners with symptoms of heat illness than in non-ill runners. Recently, it has been suggested that the rate of heat storage during exercise in the heat may be an important factor in the development of heat stroke. Therefore, we compared the effect of two rates of heat storage on eHsp72 concentration during exercise in which subjects reached the same final core temperature. We hypothesized that with a lower rate of heat storage the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
5
16
0
Order By: Relevance
“…Data from present study supports this "minimum endogenous criteria" notion (Table 2) from VHOT which elicited a greater internal temperature, rate of internal temperature rise and a greater duration at critical T rec than TEMP and HOT. Our data is supportive of the existence of minimum endogenous criteria for the induction of eHsp72 into the circulation during exercise-heat stress as suggested by Amorim et al (2008). Supporting the absence of eHsp72 increases in TEMP and HOT (T rec of 37.90±0.29°C and 38.35±0.52°C, respectively) in the present study, parallel exercise induced changes in T rec data (mean maximum T rec 38.48°C) resulting in no change in basal eHsp72 have been reported by Hom et al (2012) during treadmill walking.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Data from present study supports this "minimum endogenous criteria" notion (Table 2) from VHOT which elicited a greater internal temperature, rate of internal temperature rise and a greater duration at critical T rec than TEMP and HOT. Our data is supportive of the existence of minimum endogenous criteria for the induction of eHsp72 into the circulation during exercise-heat stress as suggested by Amorim et al (2008). Supporting the absence of eHsp72 increases in TEMP and HOT (T rec of 37.90±0.29°C and 38.35±0.52°C, respectively) in the present study, parallel exercise induced changes in T rec data (mean maximum T rec 38.48°C) resulting in no change in basal eHsp72 have been reported by Hom et al (2012) during treadmill walking.…”
Section: Discussionsupporting
confidence: 90%
“…Increased systemic eHsp72 has been shown to be exercise intensity and duration dependent in temperate conditions (Fehrenbach et al 2005), with the addition of thermal stress (evidenced by increase T rec ) further increasing the magnitude of response (Marshall et al 2006). Consequently, a heat storage independent threshold of 38.5°C (T rec ) has been postulated (Amorim et al 2008) and demonstrated central to the magnifying influence of thermal stress on eHsp72 concentrations (Amorim et al 2008), compared to moderate intensity matched exercise. Data from present study supports this "minimum endogenous criteria" notion (Table 2) from VHOT which elicited a greater internal temperature, rate of internal temperature rise and a greater duration at critical T rec than TEMP and HOT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, the development of metabolic and cardiovascular strain varied between exercise at 60% and 75% V Á o 2 max. Previous research has suggested that the expression of eHsp72 is a function of the core temperature attained following an acute bout of exercise, rather than the rate at which hyperthermia develops (i.e., the rate of heat storage) (Ruell et al 2006;Amorim et al 2008). Accordingly, a significant correlation has been noted between eHsp72 concentration and core temperature in athletes completing a race in cool environmental conditions (21°C, 33% RH and 28 km h −1 wind velocity) (Ruell et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The HSPs are a family of highly conserved stress proteins present in the cells of all living organisms [113]. It could be found to be expressed at very low levels in healthy cells to help newly synthesized proteins to fold to an appropriate special conformation.…”
Section: Thermal Resistance and Drug Resistancementioning
confidence: 99%